Analyzing the influence of internet of things (IoT) data mining in medical tourism industry - Intan Maizura, Abd Rashid; Mohammad, Rawabdeh; Anas, Al Qudah; Irza Hanie, Abu Samah; Mohammad, Harith Amlus; Wan Ahmad Fauzi, Wan Husain (AIP Publishing, 2023)
The striking around the world transmission of COVID-19 has empowered numerous governments to meddle to maintain a strategic distance from the spread of the contamination. Medical tourism could be a developing marvel with arrangement suggestions for wellbeing frameworks, especially of goal nations. Medical tourism, a quickly developing advertise, has been recognized by numerous nations as a potential segment for financial diversification. In spite of the fact that Malaysia stands out as one of the best goals of therapeutic tourism, examination with respect to its competitiveness has been constrai ned and contract in scope. An increasing number of tourist destinations and hotels are using new technology and solutions to promote their products and services. IoT represents a great opportunity for tourism and hospitality to increase customer satisfaction while simultaneously reducing operational costs. This case ponder takes a quantitative approach to distinguish and analyze the IoT time-series data variables that position Malaysia as a competitive medical tourism goal. Based on an all-encompassing approach, this ponder has appeared that coordination of differing procedures for restorative tourism improvement with sound government arrangements and proactive administration hones has driven to significant positive results towards the shared victory of tourism and healthcare segments of Malaysia.